Impact of library instruction tutorial format on student preference and performance in first-year chemistry - Stieglitz, Tara; Whitson, Lindsey (My University, 2023)
This research study investigates the effects of library instruction tutorial format (written versus video) on student preference and performance in chemistry education. The authors assessed the format of tutorials used to provide library instruction in an introductory chemistry course by observing 27 student participants as they took in instructions in either a video or a written format and then completed two chemistry information tasks. While participants expressed strong preferences for particular formats, neither the video tutorials nor the written instructions significantly improved task completion speed or performance. Rather, the authors determined that student preference alone is enough to justify the continued production of multiple versions of instructions for the same assignment.
Keywords: blended learning; information literacy tutorials; student engagement; science librarianship